If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12z + -12 + -4z = 6 + -2z + 32 Reorder the terms: -12 + 12z + -4z = 6 + -2z + 32 Combine like terms: 12z + -4z = 8z -12 + 8z = 6 + -2z + 32 Reorder the terms: -12 + 8z = 6 + 32 + -2z Combine like terms: 6 + 32 = 38 -12 + 8z = 38 + -2z Solving -12 + 8z = 38 + -2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '2z' to each side of the equation. -12 + 8z + 2z = 38 + -2z + 2z Combine like terms: 8z + 2z = 10z -12 + 10z = 38 + -2z + 2z Combine like terms: -2z + 2z = 0 -12 + 10z = 38 + 0 -12 + 10z = 38 Add '12' to each side of the equation. -12 + 12 + 10z = 38 + 12 Combine like terms: -12 + 12 = 0 0 + 10z = 38 + 12 10z = 38 + 12 Combine like terms: 38 + 12 = 50 10z = 50 Divide each side by '10'. z = 5 Simplifying z = 5
| (x^2-1)(x^2+2x+1)= | | 3x^5y^3+81x^5= | | 5y^2-5= | | -3x^2(4x^2-3x+3)= | | y^2-4y-5= | | y-8=15 | | -(6y-5)-(-5+4)=3 | | 14-x=8 | | x^2+20x-69=0 | | M^2+7m-8= | | y=6x+32 | | 3x-8=34 | | 2x/3=x/7-11 | | H=-5t^2+32t-12 | | 9x-1+3x=6x-60 | | 10/158/25= | | 2-6x=3x-4 | | 3w+1=3w+8 | | 3x+1-4=4 | | (3x^2-x)(3x-x^2)= | | 33=[a+12] | | 13x+5=10x-12 | | [x-25]=17 | | 3a+15+2a=-4a-21 | | 3b-2=2b+12 | | (4x^2-4y^2)(4x^2+4y^2)= | | -5(2n+7)-7(-n-8)=0 | | 5(2x-5)-2(x-1)-19x= | | 9+3q=-10-10q-7 | | 1.3x-3.4=0.5x+1.48 | | 3x+7=-2(2x+4)+1 | | 5+6x=25 |